Integrated collaborative care teams to enhance service delivery to youth with mental health and substance use challenges: protocol for a pragmatic randomised controlled trial. Issue 2 (6th February 2017) - Henderson, Joanna L; Cheung, Amy; Cleverley, Kristin; Chaim, Gloria; Moretti, Myla E; de Oliveira, Claire; Hawke, Lisa D; Willan, Andrew R; O'Brien, David; Heffernan, Olivia; Herzog, Tyson; Courey, Lynn; et al.
Abstract : Introduction: Among youth, the prevalence of mental health and addiction (MHA) disorders is roughly 20%, yet youth are challenged to access evidence-based services in a timely fashion. To address MHA system gaps, this study tests the benefits of an Integrated Collaborative Care Team (ICCT) model for youth with MHA challenges. A rapid, stepped-care approach geared to need in a youth-friendly environment is expected to result in better youth MHA outcomes. Moreover, the ICCT approach is expected to decrease service wait-times, be more youth-friendly and family-friendly, and be more cost-effective, providing substantial public health benefits. Methods and analysis: In partnership with four community agencies, four adolescent psychiatry hospital departments, youth and family members with lived experience of MHA service use, and other stakeholders, we have developed an innovative model of collaborative, community-based service provision involving rapid access to needs-based MHA services. A total of 500 youth presenting for hospital-based, outpatient psychiatric service will be randomised to ICCT services or hospital-based treatment as usual, following a pragmatic randomised controlled trial design. The primary outcome variable will be the youth's functioning, assessed at intake, 6 months and 12 months. Secondary outcomes will include clinical change, youth/family satisfaction and perception of care, empowerment, engagement and the incremental cost-effectiveness ratio (ICER). Intent-to-treat analyses will be used on repeated-measures data, along with cost-effectiveness and cost-utility analyses, to determine intervention effectiveness. Ethics and dissemination: Research Ethics Board approval has been received from the Centre for Addiction and Mental Health, as well as institutional ethical approval from participating community sites. This study will be conducted according to Good Clinical Practice guidelines. Participants will provide informed consent prior to study participation and data confidentiality will be ensured. A data safety monitoring panel will monitor the study. Results will be disseminated through community and peer-reviewed academic channels. Trial registration number: Clinicaltrials.gov NCT02836080 .